Man as a Responsive Participatory. Reasons for the Problem of Consciousness - Wadowski, Jan (Sensus Historiae, 2020)
The main aim of this paper is to describe humans through the prism of awareness whose origins hark back to their childhood. Awareness is understood here as a phenomenon that relates to interaction and relationship with other people. Thus, being means being aware. Therefore, consciousness is the expression of a participating community, and the boundaries of consciousness are the boundaries of our world. The article also emphasizes that consciousness manifests itself on three levels of intelligence: emotional (EQ), rational (RQ) and spiritual (SQ) and that fully adequate knowledge depends not only on the intellectual quotient, but above all on emotional and spiritual development.